Effects of bark-stripping on the water relations of Quercus suber L - Correia, O A; Oliveira, G; Martins-Loução, M a; Catarino, F M (Scientia gerundensis, 1992)
Quercus suber is the primary source of industrial cork and can produce cork every 9-10 years. The main objective of this work was to investigate the influence of bark stripping on the stomatal activity and water relations of cork-oak. For this purpose, diurnal changes on transpiration, stomatal conductance and water potencial were measured before and after bark stripping during July and August 1989 and 1990. The stripping on the trees had been done at various intensities. The water loss by the stripped surface was also measured. These results show that severe bark-stripping may lead to a decrease in stomatal conductance and considerable water losses. The stripping stress is not clearly dependent on the stripping coefficients, but rather on the water lost by the trunk which varies from tree to tree probably according to the phloemic tissues composition.
Keywords: bark-stripping; Quercus suber; Transpiration; water relations

Water relations of crok-oak (Quercus suber L.) under natural conditions - Oliveira, G; Correia, O A (Plant Ecology, 1992)
Daily and annual courses of leaf transpiration, stomatal conductance and shoot water potential of four Quercus suber individuals were compared in a semi-natural stand in southwest Portugal, from spring 1989 to early summer 1990. The trees investigated showed annual patterns typical of evergreen sclerophyllous species but varied in their range of stomatal operation. This appeared to be related to differences in hydraulic conductiv- ity in the root-to-leaf pathway. Maximum stomatal conductance and transpiration rates occurred from March to June. Water stress was found to be moderate and winter cold stress due to low air and soil temperatures appeared to have an influence on plant water balance through their effects on flow resistances. Abbreviations." g ..... stomatal conductance; g ....... maximum stomatal conductance, PAR, photosyntheti- cally active radiation; RH, relative humidity of the air; T, leaf transpiration; Ta, air temperature; TL, leaf temperature; T ........ maximum leaf transpiration; AW, air-to-leaf vapor pressure difference; W, shoot water potential; tIJPD, predawn shoot water potential; ttJMIN, minimum shoot water potential.
Keywords: Mediterranean climate; montado; Quercus suber; soil-to-leaf hydraulic conductivity; Stomatal conductance; Transpiration

Water relations of crok-oak (Quercus suber L.) under natural conditions - Oliveira, G; Correia, O A (Plant Ecology, 1992)
Daily and annual courses of leaf transpiration, stomatal conductance and shoot water potential of four Quercus suber individuals were compared in a semi-natural stand in southwest Portugal, from spring 1989 to early summer 1990. The trees investigated showed annual patterns typical of evergreen sclerophyllous species but varied in their range of stomatal operation. This appeared to be related to differences in hydraulic conductiv- ity in the root-to-leaf pathway. Maximum stomatal conductance and transpiration rates occurred from March to June. Water stress was found to be moderate and winter cold stress due to low air and soil temperatures appeared to have an influence on plant water balance through their effects on flow resistances. Abbreviations." g ..... stomatal conductance; g ....... maximum stomatal conductance, PAR, photosyntheti- cally active radiation; RH, relative humidity of the air; T, leaf transpiration; Ta, air temperature; TL, leaf temperature; T ........ maximum leaf transpiration; AW, air-to-leaf vapor pressure difference; W, shoot water potential; tIJPD, predawn shoot water potential; ttJMIN, minimum shoot water potential.
Keywords: Mediterranean climate; montado; Quercus suber; soil-to-leaf hydraulic conductivity; Stomatal conductance; Transpiration